Maritime Shipping on the Northern Sea Route: Need for Greater Emphasis on Mutual Cooperation and a Non-Negotiable Safety Culture. Part I - Jawahar BHAGWAT (Arctic and North, 2020)
The opening of the Northern Sea Route (NSR) due to the melting of the Arctic sea ice ushers in many op-portunities. The International Maritime Organization has introduced several regulations for shipping and the training of seafarers. The Northern Sea Route has several challenges concerning the infrastructure and the harsh weather conditions. The recent incident on board the Viking Sky cruise liner was a reminder of such challenges. The Norwegian authorities responded admirably, and the Search and Rescue operation was conducted with the necessary coordinated effort in the shortest possible time. Other inci-dents along the NSR and increasing ship casualties in the Arctic region have been analyzed concerning the adequacy of existing regulations. The author’s opinion is that these incidents bring out a need to examine the adequacy of the Polar code, infrastructure along the NSR, and the current state of Search and Rescue (SAR). From a practical point of view, the Norwegian experience would be of interest to all Arctic states and the IMO. The evolution of the Polar Code and the challenges in implementation are discussed. The article puts forth several recommendations for improving cooperation and safety to make the NSR a viable alternative route. This article can be used for educational purposes at universities. It is relevant for civil servants, shipping authorities, search and rescue authorities, and researchers involved in developing the Arctic sea routes and specifically the Northern Sea Route.